THE APPLICATION OF INTELLIGENT TRANSPORTATION SYSTEM (ITS) IN URBAN AREAS BASED ON PUBLIC PREFERENCES - Lestira Hariani, Mira; Novriani, Shinta; Rohman, Fathur; Farhan, Ohan (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
The application of the Intelligent Transportation System (ITS) is being widely implemented in developing cities as one of the efforts to reduce congestion in urban areas. This research aims to provide recommendations for implementing the Intelligent Transportation System (ITS) in Cirebon City based on public preferences. The method used was a questionnaire survey to find out people’s preferences for the application of ITS in Cirebon City and to see its influence on the interest in travel. Data analysis technique used is linear regression analysis with 6 (six) instruments such as realtime congestion information, availability of a navigation guide system, parking capacity information, information on the availability and schedule of public transport, realtime information on congestion and accidents and realtime supervision from the government. Based on the results of the analysis, recommendations can be given for the application of the ITS system to meet public needs. This study shows that the factors that have a significant influence on people's interest in traveling are P2 and P5, which means that the application of ITS in Cirebon City need to prioritize the availability of real-time information about congestion and accidents and the availability of abnavigation guide system